Climate Risk Profile Climate Risk Profiles for presenting key challenges posed by climate change and the impacts it might have on the agricultural sector - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
These profiles have been developed for the Kenyan Government and are being used as part of the $250 million Kenya Climate Smart Agriculture Project. In addition, they are being used by Care International in Tanzania, NIRSAL in Nigeria and GIZ across 14 countries.